Analisis Gaya Bahasa Dalam Lirik Lagu Dreamcatcher Pada Album The Beginning of The End - Ni Luh Ayu Putu Mahayuni; Umul Khasanah (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
Abstract. In song lyrics there is often a language style that is able to attract readers or listeners and add aesthetic value to the lyrics of the song. This study analyzes and describes the style of language contained in the lyrics of the Dreamcatcher songs on the album “The Beginning of The End”. The data is language style contained in 10 song lyrics. This study uses a stylistic approach with descriptive qualitative methods. After conducting research on 10 song lyrics, 27 language style data were found in the 10 song lyrics. The results of data analysis were obtained from 10 song lyrics are, 1 personification, 1 allegory, 1 antithesis, 1 synesthesia, 1 metaphor in the lyrics of Breaking Out; 1 Personification and 1 Metaphor in the lyrics of My Way~この道の先へ ~(Kono Michi no Saki e); 1 Repetition, 1 Paradox, and 1 Simile in the lyrics of Chase Me (Japanese ver.); 1 Onomatopoeia, 1 Repetition, and 1 Simile in the lyrics of Good Night (Japanese ver.); 1 Synesthesia, 1 Repetition, and 1 Onomatope in the lyrics of Wonderland (Japanese ver.); 1 Simile and 1 Meiosis in the lyrics of Piri ~ 笛を吹け~ (Japanese ver.); 1 Personification and 1 Antithesis in the lyrics of What (Japanese ver.); 2 Hyperbole, 1 Onomatope, and 1 Meiosis in the lyrics of I Miss You; 1 Metaphor in the lyrics of また一人になった (And there was no one left Japanese ver.); 1 Simile and 1 Metaphor in the lyrics of You and I (Japanese ver.). Abstrak. Dalam lirik lagu seringkali terdapat gaya bahasa yang mampu menarik pembaca atau pendengar dan menambah nilai estetika dalam lirik lagu tersebut. Penelitian ini menganalisis dan mendeskripsikan gaya bahasa yang terdapat dalam lirik lagu-lagu Dreamcatcher dalam album “The Beginning of The End”. Data berupa gaya bahasa yang terdapat dalam 10 lirik lagu. Penelitian ini menggunakan pendekatan stilistika dengan metode kualitatif deskriptif. Setelah dilakukan penelitian dari 10 lirik lagu, didapatkan 27 data gaya bahasa yang terdapat dalam 10 lirik lagu tersebut. Hasil analisis data didapatkan dari 10 lirik lagu yakni 1 Personifikasi, 1 Alegori, 1 Antitesis, 1 Sinestesia, 1 Metafora dalam lirik lagu Breaking Out; 1 Personifikasi dan 1 Metafora dalam lirik lagu My Way~この道の先へ ~(Kono Michi no Saki e); 1 Repetisi, 1 Paradoks, dan 1 Simile dalam lirik lagu Chase Me (Japanese ver.); 1 Onomatope, 1 Repetisi, dan 1 Simile dalam lirik lagu Good Night (Japanese ver.); 1 Sinestesia, 1 Repetisi, dan 1 Onomatope dalam lirik lagu Wonderland (Japanese ver.); 1 Simile dan 1 Meiosis dalam lirik lagu Piri ~ 笛を吹け~ (Japanese ver.); 1 Personifikasi dan 1 Antitesis dalam lirik lagu What (Japanese ver.); 2 Hiperbola, 1 Onomatope, dan 1 Meiosis dalam lirik lagu I Miss You; 1 Metafora dalam lirik lagu また一人になった (And there was no one left Japanese ver.); 1 Simile dan 1 Metafora dalam lirik lagu You and I (Japanese ver.)